Self-esteem and Resilience Among Students Affected by Toxic Relationships - Cindy Priscila Pantjo’u; Ratriana Yuliastuti Endang Kusumiati (Universitas PGRI Yogyakarta, 2024)
The research aims to determine the levels of self-esteem and resilience among university students who are victims of toxic relationships throughout Indonesia. This study is of a quantitative nature. The research subjects consisted of 207 students who have experienced toxic relationships. Subjects were asked to fill out an Informed Consent form as part of the research protocol. The results indicate that self-esteem is not high in cases of toxic relationships; instead, it negatively affects resilience in students involved in toxic relationships. The conclusion of the study is that the hypothesis is rejected, meaning there is no relationship between self-esteem and resilience. Keywords: self-esteem, resilience, university students who are victims of toxic relationship